Biodegradable Plastics: Biodegradation Percentage and Potential Microplastic Contamination in Seawater - Permana, Muhammad Aditya; Widjajanti, Hary; Rohendi, Dedi (Indonesian Journal of Environmental Management and Sustainability, 2023)
Increasing plastic production, which causes the problem of plastic garbage polluting the oceans, has increased the use of biodegradable plastics to address the problem. However, it is still debatable how much microplastic contamination it can cause. So, this study aims to determine the proportion of biodegradable plastics in the marine environment, identify the microplastics it produces, and analyze the relationship between the two. Seawater sampling is located in the Bangka Strait. The research was conducted in the Genetics and Biotechnology Laboratory, Department of Biology, Sriwijaya University. The biodegradable plastic test material used was made from a mixture of polyhydroxyalkanoates (PHA) and starch. Biodegradation test method using standard ASTM D6691-17 with respirometry system design. The stage of microplastic identification is carried out through filtration with a 4.75 mm-size filter; density separation using ZnCl2 solution and Whatman No. 1 filter paper; as well as visual observation of microplastics under a microscope. last Pearson Correlation analysis with bootstrap to see the relationship of the percentage of biodegradation with microplastics. The results obtained in this study were the percentage of biodegradable plastic (26.5±1.4%) and positive control kraft paper (33.2±4.2%) for 70 days, which produced 9 microplastic particles from biodegradable plastic with fragment and film types. Correlation analysis concluded that there was no relationship between the percentage of biodegradation and the microplastics produced.